Rekonstruksi Pembelajaran Baca Tulis Al-Qur’an Berbasis Media Interaktif di TPQ Desa Plemahan Jombang - Septian Ragil Anandita; Alaika M. Bagus Kurnia PS; Muhamad Iqbal Nashrullah; Mohammad Baharuddin; Ahmad Yukha Dalhari; Musbichin Musbichin; Afwa Elfira Zulfa; Amalia Nur Fadilla (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
The learning of Qur’an reading and writing at Babussalam Qur’anic Learning Center and Darus Surur Qur’anic Learning Center in Plemahan Village, Sumobito District, Jombang Regency faced challenges in the form of low student comprehension of tajwid rules and limited use of teaching media by teachers. These conditions affected the quality of Qur’anic recitation and reduced student motivation. This community service program aimed to improve students’ ability to read the Qur’an according to tajwid, provide innovative learning media, and empower teachers in managing the teaching process. The program was conducted through a participatory approach using the Participatory Action Research method, involving students, teachers, and institutional leaders. The stages of the program included problem identification, joint planning with partners, development of learning media in the form of a spiral poster of tajwid, implementation of learning activities using the media, and evaluation through pre-tests, post-tests, and satisfaction questionnaires. The results showed a significant improvement in students’ abilities, with the percentage of students able to read according to tajwid increasing from 35 percent before the program to 78 percent after the activities. Students also demonstrated higher enthusiasm in learning, while teachers gained new experiences in applying interactive teaching media. This program proved that a simple innovation can create substantial improvements in Qur’anic education in rural communities. It also fostered greater awareness of the importance of Qur’anic literacy from an early age and has the potential to be replicated in other Islamic educational institutions with similar conditions.